Growth of Escherichia coli on Short-Chain Fatty Acids: Nature of the Uptake System - Salanitro, Joseph P. (1971)
Mutants of Escherichia coli K-12 which grow on butyrate and valerate were studied with respect to uptake of these substrates. To utilize short-chain and medium-chain fatty acids, E. coli must synthesize the β-oxidation enzymes constitutively. In addition, growth on the C(4) and C(5) acids requires a second mutation which permits entry of these substrates. At pH 5, both in the parent and mutant strains, butyrate and valerate penetrate as the undissociated acids but appear not to be activated and thus inhibit growth. At pH 7, the parent strain is not permeable to the anions, whereas the mutant concentrates these substrates. There appear to be two components of the uptake system, a nonspecific diffusion component and an energy-linked activating enzyme. Two mutant types which take up short-chain fatty acids are described. One synthesizes the uptake system constitutively and is inhibited by 4-pentenoate when cultured on acetate. In the other, the uptake system is inducible, and the strain is pentenoate-resistant when grown on acetate but pentenoate-sensitive when cultured on butyrate or valerate.